Outcomes for Islet Transplantation in Donation After Circulatory Death compared with Donation after Brain Death in Australia. (July 2018) - Hawthorne, Wayne; Chew, Yi Vee; Haron, Christian; Williams, Lindy; Hitos, Kerry; Mariana, Lina; Kay, Tom; O'Connell, Philip; Loudovaris, Tom
Abstract : Introduction: Islet cell transplantation has become a clinically accepted transplant technique providing long-term insulin independence, restoring normoglycaemia and treating T1D patient's severe hypoglycaemic unawareness. Unfortunately, the significant lack of organ donors results in patients remaining on the waitlist for years. Donation after Circulatory Death (DCD) donors have been reported by other groups as having up to 60% of selected DCD islet preparations proceed to transplant with similar outcomes to donation after brain death (DBD) organs. We review our isolation and transplantation outcomes from DCD donors and compare these to DBD donors over the same time period in the Australian program. Materials and Methods: Islet donor pancreata were compared from the Australian National Islet Transplant program with direct comparison of organ donor, islet isolation variables and transplantation outcomes. Donor variables included; sex, age, weight, BMI, cause of death, CIT, WIT, pancreas weight. Isolation outcomes included; pre- and post-purification islet yield, post-culture yield, purity and viability, and transplantation outcomes such as islet number transplanted and abrogation of severe hypoglycaemic unawareness. Results and Discussion: A total of 27 DCD and 73 DBD islet donor pancreata were compared with no significant differences seen in donor characteristics between DCD and DBD. However, upon evaluation of the isolation outcomes it showed that post-purification yield (IEQ) was significantly lower from the DCD group (146, 518±28, 971) compared to the DBD group (256, 986±17, 652; P=0.001). Post-purification yield per gram of pancreas was also lower from the DCD group (2, 154±504 vs. 2, 681±372 IEQ/g); and was significant (P<0.0001). Post-culture yields in terms of total IEQ and IEQ per gram of pancreas were more than four times lower from DCD pancreata (37, 634±27, 786 IEQ and 455±305 IEQ/g) compared to DBD pancreata (234, 860±18, 132 IEQ and 2, 280±199 IEQ/g), which reached extreme significance (P<0.0001). The quality and functionality of DCD and DBD islets were also significantly different in terms of the viability (%) – P=0.017 (higher in DBD than DCD), purity (%) – P=0.001 (higher in DBD than DCD), stimulation index, and beta cell viability index outcomes were not different. The proportion of DCD islets transplanted (1/27) was significantly lower than DBD (29/73) going to transplant (OR, 0.1093; 95% CI; P=0.001). Conclusion: In the Australian setting with vast distances to ship pancreata we have had poorer outcomes from DCD pancreata for islet isolation and have thus far not yielded outcomes comparable to those from our DBD donors. Earlier intervention, the use of ante mortem heparin and faster logistics in transport may not only improve the DCD organs for transplantation but also help alleviate donor shortages allowing treatment of those with T1DM and severe hypoglycaemic unawareness.